THE TECHNIQUES USED BY J.M. RODWELL IN TRANSLATING SOME DEFENSIVE VERSES OF THE QURAN FROM ARABIC INTO ENGLISH - Arrizka Febiyani (Vivid: Journal of Language and Literature, 2014)
This article highlights the techniques used by J.M. Rodwell in translating some defensive verses of Quran from Arabic into English. The data are the defensive verses from surah Al Baqarah190-193, Al Hajj:39, and Ali Imran:200. In this research, the writer firstly analyzes the contextuall meaning of the defensive verse which is inspired by Tafsir Ibn Kathir (2009) and the history of the Prophet Muhammad by M. Husain Haikal (2006). Then the analysis focuses on the techniques used by the translator. In analyzing the techniques, there are two main theories used. The main theory is proposed by Vinay and Darbelnet (cited in Fawcett 1997) and the supporting theory is proposed by Molina and Albir (2002). The data analyzed are at word and phrase level.  The result of the analysis discovers that the contextual meaning of the verses refers to the command of war which is only permitted to those who are attacked for the purpose of self-defense and defending Islamic ideology. The techniques of translation used by Rodwell in translating them are literal translation, amplification, calque, adaptation, reduction, transposition, compensation, and modulation.Key terms: the Quran, defensive verse, techniques of translation